Changing of self-care behavior by practicing 12-step program among codependents in Iran - Ajri, Zahra; Sabran, Mohammad Shatar (Marsland Press, 2011)
Promoting positive sense of self and taking care of self among people are important factors in order to achieve health promotion in every community. As self-forgetting is special character among codependents, so this study aims to find differences of self-care behavior by comparing families of addicts/alcoholics who practice the "12-step program" and who do not. In other words, this study investigates whether "12-step program" can empower families of addicts/alcoholic to change their self-care style or not. Theory of empowerment is the key theory to conduct this study. The findings of this study indicate that “12-step program” is effectiveness program to enable codependents to having positive self-image. In other words, independent samples t-test reveals that codependents who practice the "12-step program" take care of themselves more than another group who did not practice this program.